2008
DOI: 10.3171/spi/2008/9/9/285
|View full text |Cite
|
Sign up to set email alerts
|

Herniated and spondylotic intervertebral discs of the human cervical spine: histological and immunohistological findings in 500 en bloc surgical samples

Abstract: Object In this paper the authors' goal was to identify histological and immunohistochemical differences between cervical disc herniation and spondylosis. Methods A total of 500 cervical intervertebral discs were excised from 364 patients: 198 patients with disc herniation and 166 patients with spondylosis. We examined en bloc samples of endplate-ligament-disc complexes. Types of herniation and graded deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 34 publications
1
101
0
4
Order By: Relevance
“…Immunoreactivity for some cytokines (IL-4, IL-6, IL-12, IFN-g, TNF-a) seemed modest but evident in herniated and degenerated discs, with substantial macrophage infiltration [116,122]. Also, pathologic discs highly expressed IL-17, suggesting the involvement of Th17 lymphocytes in disc herniation [123].…”
Section: Degenerated Samplesmentioning
confidence: 99%
“…Immunoreactivity for some cytokines (IL-4, IL-6, IL-12, IFN-g, TNF-a) seemed modest but evident in herniated and degenerated discs, with substantial macrophage infiltration [116,122]. Also, pathologic discs highly expressed IL-17, suggesting the involvement of Th17 lymphocytes in disc herniation [123].…”
Section: Degenerated Samplesmentioning
confidence: 99%
“…Cervical spondylosis often manifests with spastic tetraparesis with varying degrees of sensory dysfunction [6,10,11,14,26,45]. Crandall et al [10] indicated that somewhat less than 7% of patients with cervical spondylotic myelopathy present with minimal sensation loss, and classified this subtype of the disorder as cervical spondylotic amyotrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous factors, including crystal deposits in the annulus of human intervertebral discs and ECM breakdown products, can trigger the IVD inflammatory response (30,31). Various proinflammatory cytokines, including IL-1β, IL-6, IL-12 and TNF-α, were significantly increased due to immunoreactivity in herniated and generative IVD tissues (32,33). To investigate the role of miR-27a in IDD, a stable miR-27a-knockdown NP cell line was generated by transfection with an miR-27a inhibitor, and an IDD cell model was established by LPS stimulation of cells.…”
Section: Discussionmentioning
confidence: 99%